Dynamics Governance in BUMDES Management: Study of BUMDES Tugu Kuning, Pacitan, East Java - I Made Arie Widyasthana Wartana Putra; Sajida Sajida; Ahmad Luthfi; Bella Novita Hardianti; Aprillia Absharina (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
Research on BUMDes management aims to see how the village government implements village management policies for community economic activities, this article can be used to study village management governance through the several stakeholders involved. The study used is a concept in collaborative governance to identify the challenges faced in managing the economic activities of rural communities, so that they can provide some suggestions for strengthening the village economic sector. The research method chosen in this research is a case study qualitative research method, with primary data sources from informants of governance actors at BUMDes Tugu Kuning. This study shows how the role of government actors in carrying out village economic activities. The results of the study show that the role of the Director of BUMDes Tugu Kuning dominates in the process of managing the village economy accompanied by the formation of new business units. As a result, the community is less involved and involved in the BUMDes institutional structure which is dominated by the BUMDes Director.